ANALYSIS OF THE EFFECT OF BRAKING LOAD ON DIESEL ENGINE PERFORMANCE - Muchlisinalahuddin, Muchlisi muchlis (Universitas Muhammadiyah Semarang, 2024)
Now, the automotive, especially in diesel engines, is experiencing a development. The use of diesel engines nowadays is also increasing because the fuel consumption of diesel motorbikes is more efficient when compared to petrol motorbikes. Meanwhile, the disc braking system has become a common choice in motorized vehicles, because when compared to other braking systems. However, the impact of loading on the performance of diesel engines with disc braking systems on motorbikes still requires more in-depth research. The research method used is the test and comparison method, where a diesel motorbike is tested by adding a load in the form of motorcycle braking and comparing fuel between dexlite and diesel. The test results between diesel fuel and dexlite showed that dexlite fuel was better than diesel fuel. The addition of load results in a decrease in engine speed, where the rotation produced by dexlite fuel is greater than diesel fuel, while the torque and power of the engine will increase where the torque and power produced by dexlite fuel is greater than diesel fuel and the ratio between diesel fuel and dexlite shows that dexlite fuel is more efficient than diesel fuel.